Pengaruh Promosi dan Kualitas Pelayanan terhadap Minat Siswa Menggunakan Produk Tabungan SIPINTAR PT. Bank Perkreditan Rakyat Pembangunan Kerinci - Sarmigi, Elex; Mahabbati, Suci; Mailindra, Wiyan; Bustami, Alek Wissalam; Ashari, Annisa Diyah; Fadlillah, Septi Husnah (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2023)
This study aimed to assess the impact of promotion and service quality on students' interest in choosing SIPINTAR products at PT. Bank Perkreditan Rakyat Pembangunan Kerinci. The research employed a quantitative approach with a survey design, involving 60 students in Kerinci Regency using the convenience sampling method. Data analysis utilized multiple linear analysis, and hypothesis testing involved the t-test and F-test with IBM SPSS 26. The findings revealed that promotion had a positive and significant impact on students' interest in using SIPINTAR products, while service quality did not significantly influence students' interest at PT. Kerinci Development People's Credit Bank. The F-test indicated that promotion and service quality jointly have a significant impact on using PT. SIPINTAR products at Kerinci Development People's Credit Bank, with a magnitude of influence at 20.6%. Despite the limitation of focusing solely on promotion and service quality in influencing savings intentions, the research provides valuable insights for the development of banking businesses, especially regional banks.